Peningkatan Keterampilan Guru PAUD Melalui Kewirausahaan Kreatif Dan Edukatif - Mahardika Agung Madepo; Lina Budiarti; Lidya Verawati (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Early Childhood Education (ECE) teachers in Indonesia often struggle with a lack of creative teaching materials and low income. This community program aimed to tackle both problems at once through hands-on training in education and entrepreneurship. 30 PAUD teachers from HIMPAUDI Kecamatan Sungai Ambawang, Kubu Raya Regency, joined the program on November 1, 2025. Two main sessions were held: one focused on making Educational Play Tools (EPT) from recycled materials, and another on basic entrepreneurship and digital marketing. Teachers were introduced to the